Comparative study on growth of different mutants Japanese quail in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
This study was conducted to find out the comparative growth performance of six color mutants Japanese quail in Bangladesh. Under this experiment the mortality had shown no significant differences among different isolated plumage color mutants (p>0.05). At day- old it is clear that day- old weight was superior in BB- Black than other mutants (p